التوصیف الفیزیائي-الكیمیائي والحسي للسكر المستخرج من قصب السكر المزروع بمنطقة وادي سوف - عدایكة, سها (Université of eloued جامعة الوادي, 2025)
The study aims to characterize the physicochemival and sensory characteristics of sugra extracted from sugar cane Saccharum officinarum cultivated in El-oued Algeria . We calculated the yield of the sugar cane plant for brown sugar, the ratio was 13% and the proportion of non-sugar is 1%. The results of the refractometer also showed the percentage of sucrose in the brown sugar solution produced with a concentration of 10% is 60% - 70% The results of the polarization device also showed that the polarization of produced and commercial brown sugar has similar values when produced sugar 5% was 761.7 degrees and commercial Brown sugar 10% was 345.87 degrees. The results of test selection showed that there is no sensory difference between produced and commercial brown sugar Except in the form, if the brown sugar produced is not crystallized, and commercial brown sugar is crystallized
التنوع البيئي و فزيولوجيا النبات
Keywords: قصب السكر; Saccharum officinarum